2011
DOI: 10.1186/1471-2229-11-182
|View full text |Cite
|
Sign up to set email alerts
|

Fruit development of the diploid kiwifruit, Actinidia chinensis 'Hort16A'

Abstract: BackgroundWith the advent of high throughput genomic tools, it is now possible to undertake detailed molecular studies of individual species outside traditional model organisms. Combined with a good understanding of physiological processes, these tools allow researchers to explore natural diversity, giving a better understanding of biological mechanisms. Here a detailed study of fruit development from anthesis through to fruit senescence is presented for a non-model organism, kiwifruit, Actinidia chinensis ('H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
111
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 45 publications
14
111
0
9
Order By: Relevance
“…However, invariable firmness remained at approximately 1500 N in the core on October 24. This softening pattern is similar to that of 'Hort16A' kiwifruit (A. chinensis) on vines (Richardson et al, 2011). However, the application of exogenous ethylene rapidly accelerates softening, and core firmness was less than 5 N. This result suggested that the process of fruit firmness reduction differs in an ethylene inductiondependent and an ethylene-independent manner.…”
Section: Namesupporting
confidence: 50%
See 1 more Smart Citation
“…However, invariable firmness remained at approximately 1500 N in the core on October 24. This softening pattern is similar to that of 'Hort16A' kiwifruit (A. chinensis) on vines (Richardson et al, 2011). However, the application of exogenous ethylene rapidly accelerates softening, and core firmness was less than 5 N. This result suggested that the process of fruit firmness reduction differs in an ethylene inductiondependent and an ethylene-independent manner.…”
Section: Namesupporting
confidence: 50%
“…In the kiwifruit variety 'Hort16A', physiological and biological analyses were performed from anthesis (0 DAA) until fruits were senescing on vines (Richardson et al, 2011). Compared with 'Hort16A', the ripening period in 'Rainbow Red' is short.…”
Section: Namementioning
confidence: 99%
“…2 and 3). The ability of ethylene/propylene treatment to induce a drastic decrease in firmness before the initiation of autocatalytic ethylene has similarly been observed in 'Hayward' Taglienti et al, 2009;Yin et al, 2008), 'Hort16A' (Richardson et al, 2011), and 'Sanuki Gold' kiwifruit (Mworia et al, 2010(Mworia et al, , 2012. This suggests that kiwifruit exhibits a time lag between fruit softening and ethylene biosynthesis during ripening, unlike most climacteric fruit such as tomato, banana, pear, and avocado, in which softening is synchronized with the induction of endogenous ethylene.…”
Section: Effects Of Propylene and 1-mcp Treatments On Kiwifruit Ripeningmentioning
confidence: 78%
“…This signifies that the accumulation of cellular propylene during treatment triggers the kiwifruit softening process without inducing any detectable levels of ethylene, but upon its withdrawal, these softening processes are hampered. Richardson et al (2011) demonstrated that, when 'Hort16A' kiwifruit was treated with ethylene for different durations of 12 h, 24 h, and 36 h, ethylene production was initiated earlier in kiwifruit treated for 36 h (after 1 day) than in fruit treated for 24 h (between 1 and 7 days), and no ethylene production was detected in fruit treated with ethylene for 12 h. Fruit treated with ethylene continuously had a drastic decrease in firmness compared with the case upon short exposure to ethylene for 12 h without the detection of ethylene. In the present study, fruit treated with propylene continuously and for 48 h reached the propylene threshold required to trigger complete fruit softening, whereas exposure to propylene for 12 h or 24 h induced limited softening, probably due to the absence of autocatalytic ethylene.…”
Section: Effects Of Propylene and 1-mcp Treatments On Kiwifruit Ripeningmentioning
confidence: 99%
See 1 more Smart Citation